Microstructural Characteristics and Mechanical Properties of a Novel Extruded Dilute Mg–Sn–Mn–Ca Alloy - Zhang, Ming-ya; Hao, Mei-juan; Cheng, Wei-li; Li, Jinghui; Guo, Chen; Niu, Xiao-feng; Wang, Hong-xia; Wang, Li-fei (Frontiers in Materials, 2019)
A novel dilute Mg-Sn-Mn-Ca (TMX) alloy system was developed and subjected to extrusion with a relatively high extrusion ratio of 36. The grain structure, nanoscale precipitates, texture, and tensile properties of the extruded dilute alloy were investigated. The results indicated that complete dynamic recrystallization (DRX) together with some nanoscale and/or sub-microscale Mg2Sn and Mg2Ca precipitates could be obtained after extrusion. The tensile yield strength, ultimate tensile strength and elongation of the extruded dilute alloy were 213 and 266 MPa, and 21%, respectively. The correlation between microstructural characteristics and properties was also discussed.